Grasping Digitalization in the Working World: An Example From the German National Educational Panel Study; Die Erfassung von Digitalisierung in der Arbeitswelt: Ein Beispiel aus dem Nationalen Bildungspanel - Teresa Sophie Friedrich; Marie-Christine Laible; Reinhard Pollak; Sebastian Schongen; Benjamin Schulz; Basha Vicari (Soziale Welt, 2021)
Digitalization and automation have increased substantially in recent years and are reshaping the working world. These fundamental changes alter employee training needs and training programs. They create new employment opportunities, may cause excessive demands or raise fears of job loss. The extent of the societal transitions induced by the ongoing digitalization call for high-quality research data. In this paper, we introduce a new multi-dimensional survey module on digitalization and its consequences for the working world, which has recently been implemented in the adult cohorts of the German National Educational Panel Study (NEPS). We show how well and for which employee groups the newly developed survey questions capture experiences with digital technologies at the workplace. We test for the applicability of the instrument with regard to gender, age, education, and job tasks and show that it predicts employee's actual participation in further training. Moreover, we show the potential that results from the combination of the new survey module with further key strengths of the NEPS data such as its life-course or competence measures. – – Digitalisierung, der Einsatz vernetzter digitaler Technologien und Automatisierung haben in den letzten Jahren stark zugenommen. Sie prägen die heutige Arbeitswelt. Dieser tiefgreifende Wandel führt zu veränderten Weiterbildungsbedürfnissen und schafft neue Beschäftigungsmöglichkeiten. Aber er führt auch zu Überforderung oder der Angst vor Arbeitsplatzverlust. Das Ausmaß der durch die fortschreitende Digitalisierung induzierten gesellschaftlichen Veränderungen erfordert qualitativ hochwertige Forschungsdaten. In diesem Beitrag stellen wir ein neues mehrdimensionales Messinstrument zur Digitalisierung der Arbeitswelt vor, das in den Erwachsenenkohorten des Nationalen Bildungspanels (NEPS) implementiert wurde. Wir zeigen, wie gut und für welche Beschäftigtengruppen die neu entwickelten Items die Alltagsrealität am Arbeitsplatz abbilden. Wir prüfen die Anwendbarkeit des Instruments im Hinblick auf Geschlecht, Alter, Ausbildung und Aufgaben im Beruf und zeigen, dass es die tatsächliche Weiterbildungsbeteiligung von Beschäftigten vorhersagt. Darüber hinaus zeigen wir das Potenzial auf, das sich aus der Kombination der neu implementierten Items mit weiteren zentralen Stärken der NEPS-Daten - wie der Lebensverlaufserfassung und Kompetenzmessung - ergibt.
doi:10.7802/2362
Keywords: 300; digitalization; job tasks; further education and training; survey questions; NEPS; Digitalisierung; Weiterbildung; Instrumentenentwicklung